Experimental investigation on biodiesel production through simultaneous esterification and transesterification using mixed rare earth catalysts - Wilasinee Kingkam; Sudarat Issarapanacheewin; Sasikarn Nuchdang; Phakkhananan Pakawanit; Vichai Puripunyavanich; Dussadee Rattanaphra (Energy Reports, 2022)
In this study, biodiesel production through simultaneous esterification and transesterification of palm oil with 10 wt% of oleic acid using the mixed rare earth catalyst was investigated. The mixed rare earth catalysts were prepared via the co-precipitation method. The effects of the precipitating parameters such as temperature, stirring speed and pH on the physicochemical and morphology of the catalysts were studied. All catalysts were thoroughly characterized using X-ray diffraction (XRD), scanning electron microscopy-energy dispersive spectrometer (SEM-EDS), fourier transform-infrared spectroscopy (FTIR), N2adsorption/desorption, CO2 temperature programmed desorption (CO2-TPD) and NH3 temperature programmed desorption. (NH3-TPD). The results indicated that the mixed rare earth catalyst prepared under the precipitation conditions: at pH 9, a stirring of 400 rpm and temperature of 30 °C showed the highest catalytic of 90% FAME content. High surface area of the catalyst, a significant larger amount of Ce and La contents in the catalyst and an appropriate amount of acid and basic sites on the catalyst led to the high catalytic activity. The catalyst could also accelerate the initial reaction rate to achieve the high FAME content of 50% within 30 min.